Climatic Impacts of Wind-Wave-Wake Interactions in Offshore Wind Farms - Fischereit, Jana; Larsén, Xiaoli Guo; Hahmann, Andrea N. (Frontiers in Energy Research, 2022)
Accurate wind resource assessments are necessary for cost effective offshore wind energy developments. The wind field offshore depends on the sea state. In coastal areas, where wind farms are usually built today, wind and waves are often not in full balance. In addition, wind farms modify their surrounding wind and turbulence field, especially downwind. These wind farm wakes, in turn, interact with the wave field, creating a complex dynamical system. To fully capture the dynamics in such a system in a realistic way, a coupled atmosphere-wave modelling system equipped with a wind farm parameterization should be applied. However, most conventional resource assessment relies on standalone atmosphere model simulations. We compare the wind-wave-wake climate predicted from a coupled modelling system, to one predicted from a standalone atmosphere model. Using a measurement-driven statistical-dynamical downscaling method, we show that about 180 simulation days are enough to represent the wind- and wave-climate, as well as the relation between those two, for the German Bight. We simulate these representative days with the atmosphere-wave coupled and the uncoupled modelling system. We perform simulations both without wind farms as well as parameterizing the existing wind farms as of July 2020. On a climatic average, wind resources derived from the coupled modelling system are reduced by 1 % in 100 m over the sea compared to the uncoupled modelling system. In the area surrounding the wind farm the resources are further reduced. While the climatic reduction is relatively small, wind speed differences between the coupled and uncoupled modelling systems differ by more than 20 % on a 10-minute time-scale. The turbulent kinetic energy derived from the coupled system is higher, which contributes to a more efficient wake dissipation on average and thus slightly smaller wake-affected areas in the coupled system. Neighbouring wind farms reduce wind resources of surrounding farms by up to 10 %. The wind farm wakes reduce significant wave height by up to 3.5 %. The study shows the potential of statistical-dynamical downscaling and coupled atmosphere-wave-wake modelling for offshore wind resource assessment and physical environmental impact studies.